2017
DOI: 10.1186/s12906-017-1909-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chinese medicinal herbs on expression of brain-derived Neurotrophic factor (BDNF) and its interaction with human breast cancer MDA-MB-231 cells and endothelial HUVECs

Abstract: BackgroundOur previous study demonstrated that an up-regulation of the Brain-Derived Neurotrophic Factor (BDNF) signaling pathway is involved the mechanism causing the recurrence of triple negative breast cancer. The aim of this study is to investigate the effects of commonly used Chinese medicinal herbs on MDA-MB-231 and HUVEC cells and how they interact with BDNF.MethodsHuman TNBC MDA-MB-231 cells and human endothelial HUVEC cells were used to explore the effect of commonly used Chinese herbal medicines on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…In vitro cell migration of MDA-MB-468/231 cells was performed using a trans-well system (ThinCertTM cell culture inserts, 24 well, 8 µm, Greiner bio-one, Switzerland) [18]. In brief, MDA-MB-468/231 cells were cultured in the upper chamber and different doses of IL-17A (0-, 1-, 10 ng/mL) were administrated in the lower chamber.…”
Section: Cell Migration Assaymentioning
confidence: 99%
“…In vitro cell migration of MDA-MB-468/231 cells was performed using a trans-well system (ThinCertTM cell culture inserts, 24 well, 8 µm, Greiner bio-one, Switzerland) [18]. In brief, MDA-MB-468/231 cells were cultured in the upper chamber and different doses of IL-17A (0-, 1-, 10 ng/mL) were administrated in the lower chamber.…”
Section: Cell Migration Assaymentioning
confidence: 99%
“…5 A preclinical study revealed that certain CHM ingredients may activate the brain-derived neurotrophic factor signaling pathway in patients with triple-negative breast cancer, thus increasing the risk of recurrence or metastasis. 6 Taiwan's National Health Insurance (NHI) program covers traditional Chinese medicine (TCM) therapy. Between 1996 and 2001, more than 60% of all patients made claims for TCM therapy through the NHI program; of the TCM users, 85.9% received CHM therapy.…”
Section: Introductionmentioning
confidence: 99%
“…5 A preclinical study revealed that certain CHM ingredients may activate the brain-derived neurotrophic factor signaling pathway in patients with triple-negative breast cancer, thus increasing the risk of recurrence or metastasis. 6…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been increased scientific interest in the study of phytochemicals from natural plant resources as complementary anticancer compounds due to their high bioavailability, minimal side effects (compared to the chemodrugs) and, most importantly, cost effectiveness. Several studies have validated the role of medicinal plants in prevention and treatment of various cancer models [8][9][10], setting new possibilities for alternative cancer therapies. In this study, the anti-cancer therapeutic role of baicalein, an active compound found abundantly in Oroxylum indicum (L.) Benth.…”
Section: Introductionmentioning
confidence: 99%